1994
DOI: 10.7863/jum.1994.13.9.659
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic features of extracranial carotid dissections: 47 cases studied by angiography.

Abstract: The purpose of this prospective study was to assess the value of continuous wave Doppler velocimetry, standard duplex scanning and color Doppler flow imaging in the diagnosis of carotid dissections. From 1975 to 1993, 42 patients (mean age, 44 +/‐ 14 years) were admitted to the University Hospital of Angers for a carotid dissection studied first by ultrasonography, then defined by angiography. Five cases were bilateral. Continuous wave Doppler examination revealed signs of severe obstruction of the carotid art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 3 publications
0
38
1
4
Order By: Relevance
“…Entretanto esta seqüência apresenta algumas limitações: se o hematoma for recente (alguns dias) poderá não apresentar hipersinal e se for antigo (meses) o hematoma já poderá ter sido absorvido e não apresentar mais o hipersinal.Além disso, quando há hipersinal preenchendo toda a luz da artéria, a diferenciação entre hematoma intramural e trombo pode ser difícil 41 . Quanto ao ultra-som Doppler das artérias carótidas e vertebrais, embora possa ser útil numa avaliação inicial, alterações específicas como a visualização do hematoma intramural ou do "flap" intimal são encontrados em menos de 30% dos exames 42 , tornando quase obrigatória a complementação da investigação com AD ou RM, principalmente nos casos vertebrais, em que a sensibilidade desse método é menor.…”
Section: Discussionunclassified
“…Entretanto esta seqüência apresenta algumas limitações: se o hematoma for recente (alguns dias) poderá não apresentar hipersinal e se for antigo (meses) o hematoma já poderá ter sido absorvido e não apresentar mais o hipersinal.Além disso, quando há hipersinal preenchendo toda a luz da artéria, a diferenciação entre hematoma intramural e trombo pode ser difícil 41 . Quanto ao ultra-som Doppler das artérias carótidas e vertebrais, embora possa ser útil numa avaliação inicial, alterações específicas como a visualização do hematoma intramural ou do "flap" intimal são encontrados em menos de 30% dos exames 42 , tornando quase obrigatória a complementação da investigação com AD ou RM, principalmente nos casos vertebrais, em que a sensibilidade desse método é menor.…”
Section: Discussionunclassified
“…[151][152][153] For complete evaluation for carotid or vertebral artery dissection, CTA and MRA are the preferred modalities.…”
Section: Limitations Of Duplex Ultrasoundmentioning
confidence: 99%
“…Authors of small series only have reported the use of ultrasonography in the diagnosis and follow-up of CADs. 10,60,64,67,71 Duplex ultrasonography provides high-resolution real-time images of the CA bifurcation and proximal internal CA and has proved reliable in evaluating the presence and severity of atherosclerotic disease. Ultrasonography is noninvasive and more widely available than conventional angiography or MR angiography.…”
Section: Diagnosis Of Cadmentioning
confidence: 99%